The multidimensional clinical profile for disorders of gut-brain interaction - Preetha Iyengar; Lin Chang (Permanyer, 2024)
The biopsychosocial model highlights the complex interactions between early life factors, psychosocial factors, and physiologic mechanisms in the pathogenesis of disorders of gut-brain interaction (DGBI). The Rome IV diagnostic criteria help clinicians diagnose DGBI on the basis of gastrointestinal symptoms and duration. However, these criteria alone do not emphasize the importance of evaluating the psychosocial comorbidities, severity, and degree of impairment that underly the pathogenesis and clinically meaningful illness states of DGBI, which can inform effective and personalized management strategies. The multidimensional clinical profile (MDCP) was created by the Rome Foundation Board of Directors as a framework for clinicians to better characterize the full dimensionality of DGBI including categorical diagnosis, clinical modifiers, personal impact, psychosocial modifiers, and physiologic modifiers to guide clinical decision-making. The aim of this review is to describe the MDCP and its clinical utility through two clinical case examples of irritable bowel syndrome with predominant diarrhea and functional constipation.